From Punishment to Healing: The Transformative Power of Restorative Justice - Karimullah, Suud Sarim (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Conventional criminal justice systems are often dominated by punitive approaches, which focus more on punishing offenders as a form of revenge and their separation from society. However, this approach has drawbacks in achieving broader goals, such as victim recovery, reducing recidivism rates, and building safer communities.Purposes of the Research: This study discusses the power of restorative justice transformation in changing the paradigm from punishment to healing. Restorative justice offers an alternative approach to responsibility, reconciliation, and healing. Methods of the Research: Literature research methods are used to understand restorative justice, including its concepts, practices, impacts, challenges, and benefits. Literature Data is systematically identified, collated, and analyzed.Results of the Research: Restorative justice is a powerful approach to changing judicial paradigms, with its principles emphasizing reconciliation, responsibility, and participation. The impact of restorative justice on perpetrators includes behavior change and responsibility, while on victims, it includes recovery and reconciliation. Implementing restorative justice requires collaboration, adequate resources, and active participation from stakeholders. Restorative justice has the potential to create a more humane, equitable, and sustainable justice system, as well as bring recovery and reconciliation to individuals and communities affected by crime.